Antibacterial and anti-inflammatory potential of three sea cucumber species from Tukuran, Zamboanga del Sur, Mindanao, Philippines - MARY GRACE EREGUERO; CHONA GELANI; RODELYN DALAYAP; MARY ANNE CORDERO; SHARON ROSE TABUGO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ereguero MG, Gelani C, Dalayap R, Cordero MA, Tabugo SR. 2023. Antibacterial and anti-inflammatory potential of three sea cucumber species from Tukuran, Zamboanga del Sur, Mindanao, Philippines. Biodiversitas 24: 2527-2535. The marine environment is a rich source of potential antibacterial and anti-inflammatory agents. This study investigated three sea cucumber species' antibacterial and anti-inflammatory activity from Tukuran, Zamboanga del Sur, Philippines. The methanol: ethyl acetate crude extracts of Holothuria scabra, Stichopus sp., and Holothuria atra were tested for their antibacterial activity against gram-negative (Pseudomonas aeruginosa, Escherichia coli) and gram-positive (Staphylococcus aureus, Bacillus subtilis) bacteria using modified microtiter plate method. Results revealed that sea cucumber extracts have MIC values of 0.0008-0.0944 mg/mL. One-way ANOVA results revealed a p value <0.05, and Tukey’s pairwise result confirmed that the antibacterial activity of H. scabra extract is not comparable with Ciprofloxacin (p value <0.05). However, Stichopus sp., and H. atra (1) and H. atra (2) revealed a comparable antibacterial activity with Ciprofloxacin (p value >0.05). The crude extracts were also evaluated for in vitro anti-inflammatory activity using the albumin denaturation method. The results showed a percentage inhibition within the range from 44.50-49.69%, 44.74-51.44%, 31.82-49.48%, and 49.16-52.15% inhibition at 200-, 100-, 50-, and 25 ppm, respectively. One-way ANOVA and Tukey’s pairwise result revealed that the sea cucumber extracts showed a comparable percent inhibition with the positive controls, Celecoxib and Diclofenac sodium, at 200 ppm. This study revealed sea cucumber crude extracts as a potential antibacterial and anti-inflammatory agent.